2022
DOI: 10.1039/d1ra08977c
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and temperature dependence of fluorescence anisotropy of green fluorescent protein

Abstract: Effect of high hydrostatic pressure and temperature on the steady state fluorescence anisotropy of Green Fluorescent Protein (GFP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…This difference in the contribution is mainly due to the large T / η rather than the temperature-dependent viscosity ∂η / ∂T. The importance of the viscosity term was also implied by Kaur et al, (18) and our study quantitatively supports this. The disagreement for the FITC-dextran conjugates may be due to the complex structure of dextran, which consists of many glucose molecules linked by linear and branched bonds.…”
Section: Probe Moleculesupporting
confidence: 90%
See 2 more Smart Citations
“…This difference in the contribution is mainly due to the large T / η rather than the temperature-dependent viscosity ∂η / ∂T. The importance of the viscosity term was also implied by Kaur et al, (18) and our study quantitatively supports this. The disagreement for the FITC-dextran conjugates may be due to the complex structure of dextran, which consists of many glucose molecules linked by linear and branched bonds.…”
Section: Probe Moleculesupporting
confidence: 90%
“…The fluorescence lifetime is τ, Boltzmann's constant is k B , and the hydrodynamic volume of the fluorescent molecule is V. Equation ( 2) explicitly indicates that FA is a temperature-sensitive parameter. (11,18) It can also be confirmed that FA depends on the sample fluorescence lifetime, molecular size, and viscosity. In this study, we compared the temperature sensitivity of FA by changing the molecular size as a probe-dependent parameter and the viscosity as a solvent-dependent parameter.…”
Section: Perrin's Equation and Temperature Sensitivitymentioning
confidence: 80%
See 1 more Smart Citation
“…Many cryoprotectants have been used for cryohistological: glycerol (Kitin et al 2020), su crose (Lestari et al 2018), dimethyl sulfocide (DMSO) (Bekheet et al 2020), polyvinylpyrrolidone (PVP) (Soon thornkalump et al 2020), and polyethylene glycol (PEG) (Roqueborda et al 2021). However, Kaur et al (2022) reported that the steady state fluorescence anisotropy of GFP is about 10-70 °C.…”
Section: Discussionmentioning
confidence: 99%